Answer:
Step-by-step explanation
Standard form
[tex]y" + P(x)y'+Q(x) y =0[/tex]
Hence your P(t) = -3, Q(t) = 2
[tex]y(x) = Vy_1(x)\rightarrow y'(x) = V'y_1(x) + Vy_1'(x) ~~~and ~~~y"(x) = v"y_1(x) +2V'y_1'(x)+Vy_1(x)[/tex]
After replacing all y", y' and y to homogeneous part, you will have
[tex]e^x V"+5e^x V'=0\longleftrightarrow V"+5V'=0[/tex] because [tex]e^x\ne 0[/tex]
Let U = V'
[tex]U'+5U=0\rightarrow \frac{du}{u}=-5dx[/tex] .
[tex]lnu= -5x \rightarrow u = e^{-5x}[/tex]
Replace back,
[tex]V' = e^{-5x}\rightarrow V= \frac{e^{-5x}}{-5}[/tex]
then
[tex]y(x) = V y_1(x) = \frac{e^{-4x}}{-5}[/tex]
So, general solution of the ODE is
[tex]Ay_1(x) + By_2(x)[/tex]
Particular solution is just take derivative of the general one twice and plug back into the original ODE to find A and B
You can finish it by yourself. Let me know if you need more help